The State of the Art - Danto, Arthur C. 1924-2013 (New York Prentice Hall, 1987)
An art critic who weaves Nietzsche and Hegel into journalism is rare, but Danto, who writes for the Nation, turns out philosophically informed criticism with pungency and bite. He reminds us that most 20th century art, until recently, has been revolutionary or religious, viewed by its makers as a means of spiritual transformation. He skewers the fashionable and chic with critiques of Julian Schnabel, Jonathan Borofsky and others. His send-ups are all the more devastating for being good-natured and philosophically anchored. Sometimes his approach is pedantic and the reader grows impatient. Danto is equally interesting whether he is reassessing famous masters (Chagall, Van Gogh, Durer) or unraveling contemporaries whom he admires (Robert Motherwell, Leon Golub). He provocatively argues that recent major exhibitions on primitivism in modern art and on India were stupendously misguided. Photos not seen by PW. Copyright 1987 Reed Business Information, Inc.
Keywords: 20th Century (1901-2000); Esthetics; Fine art